DISTRIBUSI BAHAN ORGANIK DI BENDUNGAN CIRATA - Soetrisno, Yudhi (Jurnal Hidrosfir Indonesia, 2009)
It has been widely known that the Cirata reservoir has beenheavily polluted by waste from aquaculture and Industry. Thisresearch was conducted to determine the spread of organic matterin the waters of the Cirata reservoir The result revealed that Cirata reservoir has heavily pollutedby organic waste, so since the year 1997 has become a hypertrophicwaters, and until the year 2003 the situation has not changed. If thepollutant load is not also decrease the Cirata reservoir feared wouldturn into "a the biggest cesspool in the world. that will create variousnegative impacts, like the mass death of fish culture whichsometimes have occurred in Cirata reservoir. Organic matter (pollutant) in dam Cirata water bodiesdominated by dissolved organic matter with a range between 68,2-84,2 percent. Organic matter in the inlet water (derived from B.Saguling) tend to be greater than in the water at the outlet so thatimplied that some organic matter carried in water S. Citarum weresedimentated and decomposed in Cirata reservoir. Fraction of life particle organic matter in total organic matterin the water in the Cirata reservoir and outlets tend to be larger thanthe water in the inlet which entering water from Saguling reservoir.